2023
DOI: 10.3390/polym15224356
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Integrative Study on the Inhibitory Effects of WRR and ERW on Amyloid β Peptide (1–42) Polymerization and Cell Toxicity

Zhongyun Wu,
Lianmeng Ye,
Nan Yuan
et al.

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease and the main pathological characteristic of AD is the deposition of Aβ42 in the brain. Inhibition of Aβ42 polymerization is one of the important research directions. Due to the pathological complexity of Alzheimer’s disease, studies on Aβ42 polymerization inhibitors have not made significant progress worldwide. Using an independently constructed structure database of oligopeptides, in this study, molecular docking, umbrella sampling analysis of free energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Wu et al performed virtual screening of oligopeptides against Aβ 42 polymerization using molecular docking (Table ). The lead tripeptides, Glu-Arg-Trp (ERW) and Trp-Arg-Arg (WRR), showed interactions with Phe19, IIe32, Leu34, and Met35 and Phe4, Ala30, and Met35 residues of Aβ 42 , respectively. The umbrella sampling calculations indicated that WRR binds most strongly with Aβ 42 , and binding free energy was noted to be 6.0 kcal/mol.…”
Section: Multifunctional Peptide-based Inhibitors Against Admentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al performed virtual screening of oligopeptides against Aβ 42 polymerization using molecular docking (Table ). The lead tripeptides, Glu-Arg-Trp (ERW) and Trp-Arg-Arg (WRR), showed interactions with Phe19, IIe32, Leu34, and Met35 and Phe4, Ala30, and Met35 residues of Aβ 42 , respectively. The umbrella sampling calculations indicated that WRR binds most strongly with Aβ 42 , and binding free energy was noted to be 6.0 kcal/mol.…”
Section: Multifunctional Peptide-based Inhibitors Against Admentioning
confidence: 99%
“…Several MTD peptides against AD reported in this review can themselves act as guiding chemotypes for the development of potent therapeutics against AD. 46 tested in cellular model (SH-SY5Y cells) LA-GPE 47 tested in cellular model (SH-SY5Y cells) GS(HQ)H 48 tested in cellular model (SH-SY5Y cells) ZW1 51 tested in transgenic mouse model GGH 52 tested in cellular model (PC12 cells) P6 53 tested in cellular model (PC12 cells) GR 54,55 tested in cellular model (PC12 cells) and rat model GSH-LD 56 tested in cellular model (U937 cell lines) LK7-HH 58 tested in cellular model (PC12 cells) Car-LK7 59 tested in cellular model (SH-SY5Y cells) RK10 61 tested in cellular model (SH-SY5Y cells) rk10 62 tested in cellular model (SH-SY5Y cells) Glupep 66 tested in cellular model (PC12 cells) MPLT3, MPGLT 67 tested in cellular model (SH-SY5Y cells) PA 19 fCP 68 tested in cellular model (N2a cells) Semax 69 tested in cellular model (SH-SY5Y cells) DS2 70 tested in cellular model (SH-SY5Y cells) WRR, ERW 71 tested in cellular model (SH-SY5Y cells) TH006 74 tested in rat model AI 75 tested in cellular model (PC12 cells) LE6 76 tested in cellular model (PC12 cells) SLKP 77 tested in cellular model (PC12 cells) NVR 78 tested in cellular model (PC12 cells) W3 79 tested in brine shrimp RA-1 80 tested in cellular model (PC12 cells) LME-tet 85 tested in cellular model (N2a cells)…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%